Análisis financiero a la empresa de Servicios de Ingeniería y Consultoría Electritelecom Cía. Ltda. de la ciudad de Loja, periodos 2021-2022 - Tenesaca Campoverde, Milena Briggette (2024)
In the Curricular Integration Work, we determined the economic and financial situation of the company through the application of vertical and horizontal analysis and financial indicators to know the liquidity, solvency, management, and profitability; in the vertical analysis, we identified a greater concentration in the Current Assets in 2021, a situation that changes in 2022 since the highest amount concentrated in the Non-Current Assets, because of the increase in Income through the services rendered for which the company acquires property, plant, and equipment, the company finances its assets mainly with debt, given that in 2021 the Non-Current Liabilities register 46.97% and in 2022 was funded in the long term with 55.29%, the difference corresponds to Current Liabilities. Regarding the economic aspect in 2022, there was a profit growth of 286.81%, significantly improving in 2021. To achieve these, partners decided to reduce expenses by -40.03%, and the accounts that had the highest impact were selling and administrative costs; the critical indicator was patrimonial strength in 2021 was - 1.72, for 2022 the indicator was 3.64; this improvement was a consequence of the contribution made by the partners, as a result of the appropriate decisions made by the partners, the average collection period indicator for 2022 decreased by 26 days, which allowed a cash flow in a shorter time in favor of the company and thus the ability to cover its costs and expenses.